1997
DOI: 10.1111/j.1600-0447.1997.tb09915.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties of phototherapy for seasonal affective disorder: a meta‐analvsis

Abstract: The general therapeutic effect of light on seasonal affective disorder (SAD) has been widely acknowledged. However, the antidepressant effect of light does not seem to be the same for different spectra of light. In this study, the authors attempted to study the spectral properties of phototherapy for SAD using a meta-analytical procedure. The findings suggested that light of short to medium wavelengths (blue/green/yellow) seem to be essential for the therapeutic effect of light on SAD. Red wavelengths were rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Additional studies showed green fluorescent light to be therapeutically more potent than an equal photon dose of red fluorescent light (Oren et al 1991). A later meta-analysis reported that red wavelengths are relatively ineffective in the treatment of SAD while short and medium wavelengths of visible light produced antidepressant effects (Lee et al 1997). In some of the studies reviewed, however, red light was studied at dimmer intensities than was light of other wavelengths.…”
Section: ___________________________________________mentioning
confidence: 99%
“…Additional studies showed green fluorescent light to be therapeutically more potent than an equal photon dose of red fluorescent light (Oren et al 1991). A later meta-analysis reported that red wavelengths are relatively ineffective in the treatment of SAD while short and medium wavelengths of visible light produced antidepressant effects (Lee et al 1997). In some of the studies reviewed, however, red light was studied at dimmer intensities than was light of other wavelengths.…”
Section: ___________________________________________mentioning
confidence: 99%
“…However, other researchers have found that morning light is comparable in efficacy to evening light or to dual morning-evening administration, replicating the findings of the skeleton photoperiod study (Lee et al, 1997). Lee et al's (1997) …”
Section: Morning Light To Phase-advance Circadian Rhythmsmentioning
confidence: 70%
“…Light may be antidepressant in SAD independent of its impact on circadian rhythms. Because light has a variety of effects on the body, researchers have attempted to manipulate several light-related parameters with the aim of alleviating SAD, such as timing, intensity, and wavelength (Lee, Chan, Paterson, Janzen, & Blashko, 1997;Oren et al, 1991). Research using bright light therapy to shorten the nocturnal duration of melatonin release, to simulate a summer-like photoperiod, to phaseadvance circadian rhythms and to increase the number of photons delivered to the retina is described below.…”
Section: Antidepressant Effect Of Light In Sadmentioning
confidence: 99%
See 1 more Smart Citation
“…Several animal studies have shown that the spectral composition of ambient lighting can influence the course of refractive development (Rohrer et al, 1992;Seidemann & Schaeffel, 2002;Rucker, 2013;Smith et al, 2015), and exposure to different wavelengths of light are also known to influence diurnal rhythms (Lee et al, 1997;Warman et al, 2003;Glickman et al, 2006). This suggests that the spectral content of In Chapter 2, objective light exposure data from young adults and children were acquired with a wrist-worn light sensor over a continuous 14-day period, and a detailed analysis examining the effects of sampling strategies upon metrics describing daily patterns of light exposure was conducted.…”
Section: Discussionmentioning
confidence: 99%